2007
DOI: 10.1086/516731
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Spectroscopy of Diamondoid Molecules: New Insights into the Presence of Nanodiamonds in the Interstellar Medium

Abstract: Although they are relatively different in band shape, infrared features around 3.4-3.5 m in the emission spectra of HD 97048 and Elias 1 and in the absorption spectra of various dense clouds have both been attributed to diamondoid molecules /particles. This assignment is based mainly on infrared spectra of hydrogenated diamond thin films and of diamond nanocrystals of known average size. Here we present an analysis of the astrophysical implications of recently reported solid-state 2.5-12.5 m spectra of individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
113
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(120 citation statements)
references
References 26 publications
7
113
0
Order By: Relevance
“…These sources are different from the ones previously discussed for the 21 "microns" feature. Recently, from a molecular approach, Pirali et al (2007) measured small diamondoids in the gas phase and, reported calculations, as well as attenuated total reflectance spectra for higher diamondoids. Analogues of the measured species with the same symmetry containing around 130 C atoms (e.g., C 136 H 104 ) show an intensity ratio of the 3.53 and 3.43 μm bands close to that observed in the interstellar spectra.…”
Section: (Nano-)diamondsmentioning
confidence: 99%
“…These sources are different from the ones previously discussed for the 21 "microns" feature. Recently, from a molecular approach, Pirali et al (2007) measured small diamondoids in the gas phase and, reported calculations, as well as attenuated total reflectance spectra for higher diamondoids. Analogues of the measured species with the same symmetry containing around 130 C atoms (e.g., C 136 H 104 ) show an intensity ratio of the 3.53 and 3.43 μm bands close to that observed in the interstellar spectra.…”
Section: (Nano-)diamondsmentioning
confidence: 99%
“…For example, adamantane (C 10 H 16 ), with a cage-like, full sp 3 structure, shows vibrational bands in the 3 µm region in both gas and solid phases (Oomens et al 2006;Pirali et al 2007). The C-H stretch of hydrogenated diamonds at 3.43 and 3.53 µm have been detected (Guillois, Ledoux, & Reynaud 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The hydrogenated solids comprise nanodiamonds, observed through vibration bands at 3.43 and 3.53 μm of hydrogen-terminated nanodiamonds (Chang et al 1995;Guillois et al 1999;Pirali et al 2007) in equilibrium with the stellar radiation field. They are observed close to the stars around very few objects (Habart et al 2004;Acke et al 2006;Goto et al 2009).…”
Section: Introductionmentioning
confidence: 99%